A AKAP4 do espermatozóide como biomarcador da fertilidade de touros - Zandonaide, João Pedro Brandão (2024)
Although some sires exhibit ejaculates with characteristics within the recommended standards for frozen semen, many still do not achieve satisfactory conception rates, being considered subfertile or infertile. This condition leads to significant economic losses in cattle production. To identify parameters and correlations that can elucidate issues related to infertility and are accessible in terms of cost and execution for the early determination of the insemination dose's fertility, researchers have been investigating factors and substances present in semen at proteomic, metabolomic, and genomic levels, seeking effective fertility biomarkers. The present study aimed to measure the concentration of the proAKAP4 protein in frozen semen from bulls determined to be of high and low fertility when tested in the field. High-fertility bulls had a higher concentration of proAKAP4 in semen (34.69 ± 3.57 ng/10^6 spermatozoa) compared to low-fertility bulls (19.48 ± 2.06 ng/10^6 spermatozoa) (p<0.05). Additionally, high-fertility bulls demonstrated a higher proportion of intact plasma membrane (65.83% ± 2.28) compared to those of low fertility (56.37% ± 2.12; p = 0.0052). The simultaneous analysis of damaged plasma membrane and intact acrosome (DPMIA) showed lower values for high-fertility bulls (21.2% ± 1.23) compared to low-fertility bulls (26.53% ± 1.7; p = 0.0151). In the evaluation of intact plasma membrane associated with mitochondrial potential (IPM-MP+), high-fertility bulls showed superior results (49.72% ± 2.23) compared to the low-fertility group (42.64% ± 1.75; p = 0.0205). In sperm kinetics, there was a lower presence of non-progressive cells in high-fertility bulls (59.39% ± 2.04) compared to low-fertility bulls (65.54% ± 1.87; p = 0.0358), while the opposite was observed for progressive cells (30.78% ± 1.85 and 25.29% ± 1.55; p = 0.0331). It is concluded that proAKAP4 concentration can be used as a cellular biomarker for fertility in bulls.